Predicting the effects of polychlorinated biphenyls on cetacean populations through impacts on immunity and calf survival. (February 2018) - Hall, Ailsa J.; McConnell, Bernie J.; Schwacke, Lori H.; Ylitalo, Gina M.; Williams, Rob; Rowles, Teri K.
Abstract: The potential impact of exposure to polychlorinated biphenyls (PCBs) on the health and survival of cetaceans continues to be an issue for conservation and management, yet few quantitative approaches for estimating population level effects have been developed. An individual based model (IBM) for assessing effects on both calf survival and immunity was developed and tested. Three case study species (bottlenose dolphin, humpback whale and killer whale) in four populations were taken as examples and the impact of varying levels of PCB uptake on achievable population growth was assessed. The unique aspect of the model is its ability to evaluate likely effects of immunosuppression in addition to calf survival, enabling consequences of PCB exposure on immune function on all age-classes to be explored. By incorporating quantitative tissue concentration-response functions from laboratory animal model species into an IBM framework, population trajectories were generated. Model outputs included estimated concentrations of PCBs in the blubber of females by age, which were then compared to published empirical data. Achievable population growth rates were more affected by the inclusion of effects of PCBs on immunity than on calf survival, but the magnitude depended on the virulence of any subsequent encounter with a pathogen and the proportion of the population exposed. Since the starting population parameters were from historic studies, which may already be impacted by PCBs, the results should be interpreted on a relative rather than an absolute basis. The framework will assist in providing quantitative risk assessments for populations of concern. Graphical abstract: Image 1 Highlights: An individual based model for assessing effects of PCBs on cetacean populations was developed and tested. Four case studies showed that achievable population growth rates were affected. Consequences of reduced immunity depended on pathogen virulence and the proportion of the population exposed. The framework will assist in providing quantitative risk assessments for populations of concern. Abstract : Current exposure levels of particular cetaceans to PCBs may significantly affect their population growth rates, through effects on immunity as well as calf survival.